Che Guevara: Latin America, the awakening of a continent - Ariet García, María del Carmen (2019)
The present work is part of a set of pressuposts investigated by the author with the objective of appropriating a deep look at the concerns and searches that first Ernesto Guevara will make on the context and environment of Latin America of his years youth, to follow, later --converted in Che--, greater purposes and decisions that would take him to a higher dimension marked by his unwavering determination to fight for the true sovereignty and independence of the continent. This view seen from its historical evolution, contributes to a more complete understanding to understand the purposes that it was proposed to achieve since it began its first journeys through regions, aggressive and suggestive, but all with identical results: an unstoppable commitment to man Latin American and his full liberation.